2020
DOI: 10.1186/s41983-020-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids supplementation can improve specific language impairment in preschool children: a pilot study

Abstract: Background: Speech and language are one of the higher cognitive brain functions. Language delay is one of the major concerns of child health in Egypt. Speech therapy is the standard management in language delay. Objective: We aimed to investigate the potential role of dietary supplementation with polyunsaturated fatty acids (PUFAs) in improving specific language impairment. Subjects and methods: A total of 220 children (ages 3-4) were included in this study at the Phonetics Department, Helwan School of Medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…al., 2021) omega-3 consumption promotes the improvement of executive functions and self-regulation. In turn, Yasseen et al ( 2020) (Yasseen et. al., 2020) investigated the impact of Omega-3 consumption on speech development and showed that the supplementation group improved their language quotient significantly about the control group, who went to speech therapy.…”
Section: Cognitive Performancementioning
confidence: 99%
“…al., 2021) omega-3 consumption promotes the improvement of executive functions and self-regulation. In turn, Yasseen et al ( 2020) (Yasseen et. al., 2020) investigated the impact of Omega-3 consumption on speech development and showed that the supplementation group improved their language quotient significantly about the control group, who went to speech therapy.…”
Section: Cognitive Performancementioning
confidence: 99%